Small molecules and heat treatments reverse vernalization via epigenetic modification in Arabidopsis - Nana Otsuka; Ryoya Yamaguchi; Hikaru Sawa; Naoya Kadofusa; Nanako Kato; Yasuyuki Nomura; Nobutoshi Yamaguchi; Atsushi J. Nagano; Ayato Sato; Makoto Shirakawa; Toshiro Ito (Communications Biology)
Abstract Monocarpic plants flower only once and then produce seeds. Many monocarpic plants require a cold treatment known as vernalization before they flower. This requirement delays flowering until the plant senses warm temperatures in the spring. Exposure to high temperatures following vernalization causes devernalization, which cancels the vernalized state, inhibiting flowering and promoting vegetative growth. In this study, we screened over 16,000 chemical compounds and identified five small molecules (devernalizers; DVRs) that induce devernalization in Arabidopsis thaliana at room temperature without requiring a high-temperature treatment. Treatment with DVRs reactivated the expression of FLOWERING LOCUS C (FLC), a master repressor of flowering, by reducing the deposition of repressive histone modifications, thereby delaying flowering time. Three of the DVRs identified shared two structures: a hydantoin-like region and a spiro-like carbon. Treatment with DVR06, which has a simple chemical structure containing these domains, delayed flowering time and reduced the deposition of repressive histone modifications at FLC. RNA-seq and ChIP-seq analyses revealed both shared and specific transcriptomic and epigenetic effects between DVR06- and heat-induced devernalization. Overall, our extensive chemical screening indicated that hydantoin and spiro are key chemical signatures that reduce repressive histone modifications and promote devernalization in plants.